A cross-sectional study: the impact of extreme weather, sleep quality, and physical activity - Gilang Ramadan; Giofandi Samin; Arief Ibnu Haryanto; Sulasikin Sahdi Kadir; Ardo Okilanda (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to explore the impact of extreme weather condition on sleep quality and physical activity in Gorontalo using a cross-sectional research design. The data were collected from 220 respondents aged 18-25  using the Pittsburgh Sleep Quality Index (PSQI), International Physical Activity Questionnaire (IPAQ),  and weather information from BMKG Gorontalo. The results showed that extreme weather, especially high temperatures, significantly reduced physical activity and affected sleep quality. Respondents with higher physical activity levels showed better sleep quality (lower PSQI scores). Extreme weather also reduces motivation to exercise, increasing the risk of health problems such as dehydration and heat stroke. In conclusion, public health interventions that promote physical activity and improved sleep quality during extreme weather conditions are urgently needed to reduce associated health risks. This study emphasises the importance of understanding the specific mechanisms of how extreme weather affects sleep and physical activity, and developing strategies to maintain healthy routines despite adverse weather conditions.